The effects of caffeine ingestion on time trial cycling performance - McNaughton, L. R.; Lovell, R. J.; Siegler, J.; Midgley, A. W.; Moore, L.; Bentley, D. J. (International Journal of Sports Physiology and Performance, 2008)
The purpose of this work was to determine the effects of caffeine on high intensity time trial (TT) cycling performance in well-trained subjects. Subjects: Six male cyclists with the following physical characteristics (mean ± SD) age 30.7 ± 12, height 179.3 ± 7.5 cm, mass 70.0 ± 7.5 kg, VO2max 65.0 ± 6.3 mL·kg-1·min-1 undertook three 1-h TT performances, control (C), placebo (P) and caffeine (CAF), on a Velotron cycle ergometer conducted in a double-blind, random fashion. Subjects rested for 60 min and were then given CAF or P in a dose of 6 mg·kg-1 body mass and then commenced exercise after another 60 min of rest. Before ingestion, 60 min postingestion, and at the end of the TT, finger-prick blood samples were analyzed for lactate. Results: The cyclists rode significantly further in the CAF trial (28.0 ± 1.3 km) than they did in the C (26.3 ± 1.5 km, P < .01) or P (26.4 ± 1.5 km, P < .02) trials. No differences were seen in heart rate data throughout the TT (P > .05). Blood lactate levels were significantly higher at the end of the trials than either at rest or postingestion (P < .0001), but there were no differences between the three trial groups. Conclusion: On the basis of the data, we concluded that performance was improved with the use of a caffeine supplement.